Recovery of mitochondrial DNA for systematic studies of Pentatomoidea (Hemiptera: Heteroptera): successful PCR on early 20th century dry museum specimens - Lis, Jerzy A.; Ziaja, Dariusz J.; Lis, Paweł (Zootaxa, 2011)
First molecular studies on museum specimens of five families of pentatomoid bugs, namely Cydnidae, Dinidoridae, Parastrachiidae, Tessaratomidae, and Thyreocoridae (Hemiptera: Heteroptera: Pentatomoidea), are presented, as a preliminary approach to molecular phylogenetic analyses of these families. Forty-eight pin-mounted museum specimens representing 46 pentatomoid species collected in the late 19 th and the 20 th century (more than 15 years old, the oldest specimen collected in 1894) were analyzed; and the acquisition of PCR amplifiable mitochondrial DNA (16S and/or 12S rDNA fragments) was successful from 10 specimens, i.e., 2 specimens (2 species) of Cydnidae, 4 specimens (4 species) of Dinidoridae, 1 specimen (1 species) of Parastrachiidae, 1 specimen (1 species) of Tessaratomidae, and 2 specimens (2 species) of Thyreocoridae. The oldest PCR amplifiable mtDNA sample was extracted from Strombosoma impictum (Stål) (Thyreocoridae) collected in 1932 in Zaire.